Illustration of Pareira root - Wills, George S. V. (A Manual of Vegetable Materia Medica, 1886)
A color lithograph of Pareirae radix, Pareira root. This manual identifies plants used for medicinal purposes. The focus is on plants that can be acquired through commerce in Britain and are illustrated as they would have been imported and bought, for example the opium is illustrated as a processed capsule wrapped in a poppy leaf instead of the poppy plant itself. Authored by George Sampson Valentine Wills (1849-1932). Wills was the founder and Director of the Westminster College of Chemistry and Pharmacy in London. The school was established to train druggists for examinations by the Pharmaceutical Society of Great Britain, the regulating body established in 1841.
Keywords: Botany, Medical; Medicinal plants; Botanical illustration; Materia medica, Vegetable